2013
DOI: 10.1111/hepr.12040
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic vein waveform and splenomegaly predict improvement of prothrombin time after splenectomy in hepatitis C virus‐related cirrhotic patients

Abstract: Prothrombin time and total bilirubin improve in approximately half of cirrhotic patients within a year after splenectomy. HVWF type I and splenomegaly may be predictive factors for improvement in prothrombin time after splenectomy in patients with cirrhosis due to hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…We found both late and early recurrence rates were higher in the high SV than the low SV group. Taken together, the present findings and those of previous reports suggest that SV is correlated with liver dysfunction [7, 26, 27]. Furthermore, other studies have shown that PH is associated with an increased incidence of HCC [32, 33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found both late and early recurrence rates were higher in the high SV than the low SV group. Taken together, the present findings and those of previous reports suggest that SV is correlated with liver dysfunction [7, 26, 27]. Furthermore, other studies have shown that PH is associated with an increased incidence of HCC [32, 33].…”
Section: Discussionsupporting
confidence: 89%
“…Kinjo et al showed that after splenectomy, portal flow decreases more markedly in patients with large spleens than in those with small spleens. Some other studies have suggested that liver function improves more markedly in patients with larger spleens [26, 27]. Previous studies have shown that adding splenectomy to hepatectomy in patients with HCC and hypersplenism does not improve overall survival [16, 17].…”
Section: Discussionmentioning
confidence: 99%